2022
DOI: 10.31014/aior.1993.05.02.489
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effect of Stem Education on Academic Achievement: A Meta-Analysis Study

Abstract: Countries with well-trained and qualified labor force today make a significant difference with other countries in areas such as economy, education and industry. One of the important reasons for this difference is that these countries have made innovations in the fields of science, technology and education policies as well as economy. STEM, which is composed of the abbreviations of the first letters of the words Science, Technology, Engineering and Mathematics, is an interdisciplinary approach. The aim of this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Next, it calculated the publication bias of the 11 studies that had been analyzed. Calculation of publication bias in this study with funnel plot and Roshental Fail Safe (FSN) (Chamdani et al, 2022;Zhang et al, 2015;Hidayah, 2023;Taşdemir, 2022). The results of the calculation of publication bias with funnel flot can be seen in figure 1.…”
Section: Methodsmentioning
confidence: 87%
“…Next, it calculated the publication bias of the 11 studies that had been analyzed. Calculation of publication bias in this study with funnel plot and Roshental Fail Safe (FSN) (Chamdani et al, 2022;Zhang et al, 2015;Hidayah, 2023;Taşdemir, 2022). The results of the calculation of publication bias with funnel flot can be seen in figure 1.…”
Section: Methodsmentioning
confidence: 87%
“…Next, test for hereterogenity. Heterogeneity testing serves to look at the overall influence to determine the appropriate model used in the meta-analysis (Öztop, 2023;Taşdemir, 2022). The results of the heterogeneity test can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Engaging in STEM subjects helps students develop a mindset geared towards inquiry, experimentation, and understanding complex systems (Hacioğlu & Gülhan, 2021;Topsakal et al, 2022). • Improved Academic Performance: Studies have shown that students engaged in comprehensive STEM education often perform better not only in science and mathematics but also in other academic areas, due to the interdisciplinary approach and emphasis on analytical skills (Eroğlu & Bektaş, 2022;Nağaç & Kalayci, 2021;Taşdemir, 2022). • Development of Technical Skills: STEM education equips students with specific technical skills, such as programming, data analysis, and scientific experimentation, which are increasingly important in the digital age (Baterna et al, 2020;Ow-Yeong et al, 2023).…”
Section: Effects On Student Performance and Skill Development Stem Ed...mentioning
confidence: 99%